Family Support in the Care of Patients with Type 2 Diabetes Mellitus: A Scoping Review - Setyoadi, Setyoadi; Mudianti, Jihan Faadhilah; Nifangelya, Prisilya; Ramadhania, Lailatul; Ismail, Dina Dewi Sartika Lestari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
The growing global incidence of Type 2 Diabetes Mellitus (T2DM) underscores the pressing need to investigate practical and sustainable management strategies. Type 2 diabetes mellitus (T2DM) is a chronic health condition that necessitates continuous monitoring and long-term care to maintain blood glucose levels within optimal limits. One critical factor influencing diabetes self-management is family support, which encompasses emotional, instrumental, informational, and appreciative dimensions. Family members play a crucial role in supporting individuals with T2DM by assisting with daily care routines, promoting adherence to treatment regimens, and offering motivation. This scoping review aims to critically evaluate the significance of family support as a key component in enhancing self-management among individuals diagnosed with type 2 diabetes mellitus (T2DM). It will outline the key elements of family support and investigate their relationship with diabetes-related outcomes, including glycemic control, medication adherence, and dietary adherence. The review encompasses an analysis of 15 pertinent articles retrieved from three key databases: ScienceDirect, Google Scholar, and ProQuest. The keywords employed comprised